SnO2 dye-sensitized solar cells - Wali, Qamar; Jose, Rajan (Elsevier, 2019)
This chapter presents a thorough review on the role of tin oxide (SnO2) as a photoanode, either as pure or composite, with another material in dye-sensitized solar cells (DSSCs). The research in SnO2-based DSSCs is fueled by its electron mobility, which is several orders of magnitude higher than the most successful photoanode (TiO2), so much so that the transport-driven electron recombination could be minimized. The SnO2 has been developed in diverse morphologies with differing surface and electronic properties, and, therefore, with varying photovoltaic properties. This chapter gives a thorough account on the SnO2-based DSSCs.